2012
DOI: 10.1037/a0028836
|View full text |Cite
|
Sign up to set email alerts
|

Working memory encoding and false memory in schizophrenia and bipolar disorder in a spatial delayed response task.

Abstract: Working memory (WM) impairment is a core feature of schizophrenia, but the contributions of different WM components are not yet specified. Here, we investigated the potential role of inefficient encoding in reduced WM performance in patients with schizophrenia (PSZ). Twenty-eight PSZ, 16 patients with bipolar disorder (PBP), 16 unaffected and unmedicated relatives of PSZ (REL), and 29 demographically matched healthy controls (HC) performed a spatial delayed response task with either low or high WM demands. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 73 publications
9
38
1
Order By: Relevance
“…This provides some evidence that the increased rate of false memory errors likely reflects difficulties in deploying attention, which then may lead to inefficient WM encoding. This is consistent with our previous findings indicating that the impairments in spatial WM observed in PSZ as well as healthy first-degree relatives of PSZ can be attributed at least to some degree, to deficits in processes associated with WM encoding such as less precise encoding (Lee & Park, 2005; Mayer & Park, 2012). This finding is also consistent with the results from neuroimaging studies that compared true memory and false memory responses in PSZ and observed similar activation patterns in the prefrontal cortex for both types suggesting that the mechanisms that support the maintenance of the internal representation were intact whether that representation was correctly or incorrectly encoded (Lee et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This provides some evidence that the increased rate of false memory errors likely reflects difficulties in deploying attention, which then may lead to inefficient WM encoding. This is consistent with our previous findings indicating that the impairments in spatial WM observed in PSZ as well as healthy first-degree relatives of PSZ can be attributed at least to some degree, to deficits in processes associated with WM encoding such as less precise encoding (Lee & Park, 2005; Mayer & Park, 2012). This finding is also consistent with the results from neuroimaging studies that compared true memory and false memory responses in PSZ and observed similar activation patterns in the prefrontal cortex for both types suggesting that the mechanisms that support the maintenance of the internal representation were intact whether that representation was correctly or incorrectly encoded (Lee et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…If an incorrect response was giving with confidence, this was classified as false memory, in contrast to an incorrect response that was given without confidence (incorrect/ not confident response). We were particularly interested in the rate of false memory responses because false memory errors most likely reflect a problem at the encoding stage such as less precise encoding of the stimuli as demonstrated previously in PSZ (Mayer & Park, 2012). If one successfully transfers imprecisely encoded information into WM, it is possible to maintain and retrieve this information from WM, resulting in an error response that is coupled with a high degree of confidence concerning the veracity of the response.…”
Section: Introductionmentioning
confidence: 99%
“…Although WM impairments were previously probed in SZ and BPD, comparisons across disorders have yielded inconsistent findings and the relationships between cognitive and clinical symptom domains across the psychotic variations of the disorders remain unclear (Hamilton et al, 2009;Mayer and Park, 2012;Milanovic and Vangel, 2012;Zhang et al, 2012). Discrepancy in previous studies may be due to a heterogeneous patient group and/or differences in specific task demands of the cognitive measures employed.…”
Section: Introductioncontrasting
confidence: 41%
“…In a previous study we argued that one way to distinguish error types would be by separating errors based on the declared confidence of the subjects in their responses (Cano-Colino et al, 2013). While confidence reports are increasingly being used in behavioral studies of SWM (Pessoa and Ungerleider, 2004; Middlebrooks and Sommer, 2011; Mayer and Park, 2012; Rademaker et al, 2012; Tanaka and Funahashi, 2012), interpretations suffer from our limited understanding of metacognition mechanisms. Here, we sought to explore other possible strategies to distinguish errors without using metacognition, in order to control for possible confounds and to provide simpler behavioral protocols that can be implemented more easily in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the confidence declared by subjects after erroneous responses could distinguish the behavioral effects of increased and reduced 5-HT activations, and thus lead to detecting a robust serotonergic effect on SWM. These predictions are experimentally testable, since confidence reports are being increasingly used in both human (Pessoa and Ungerleider, 2004; Mayer and Park, 2012; Rademaker et al, 2012) and animal (Middlebrooks and Sommer, 2011, 2012; Tanaka and Funahashi, 2012) studies of working memory. However, there are limitations in relying only on the confidence report to test the computational model.…”
Section: Introductionmentioning
confidence: 99%